The Mengelola Konektivitas, Mengamankan Kepentingan : Diplomasi Ekonomi Maritim Indonesia di ASEAN MTWG - Windy Dermawan; Henike Primawanti; Finska Dita Auralia (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2026)
ASEAN Connectivity is a strategic agenda aimed at strengthening regional integration through the development of physical, institutional, and people-to-people connectivity. For Indonesia as an archipelagic state, the maritime transport sector plays a crucial role in supporting regional physical connectivity. This article analyzes the role and strategies of Indonesia’s maritime economic diplomacy within the framework of ASEAN Connectivity, with particular attention to Indonesia’s participation in the ASEAN Maritime Transport Working Group (MTWG) as a sectoral cooperation forum. This study employs a qualitative approach using a literature-based design combined with policy analysis. Data are collected from official ASEAN documents, publications of relevant ministries and institutions, regional cooperation reports, and academic literature on economic diplomacy, regional connectivity, and ASEAN maritime cooperation. The data are analyzed through a descriptive-analytical method to identify Indonesia’s position, diplomatic strategies, and policy implications arising from its engagement in the ASEAN MTWG. The findings indicate that the ASEAN MTWG serves as a strategic instrument for Indonesia to advance national interests in maritime transport and connectivity while enhancing its contribution to ASEAN’s regional integration agenda. Through this forum, Indonesia seeks to align national priorities with regional objectives, particularly in maritime infrastructure development and the harmonization of maritime transport policies. However, Indonesia’s maritime economic diplomacy continues to face challenges, including disparities in capacity among ASEAN member states and complex institutional coordination. This article contributes to international relations scholarship by highlighting the importance of ASEAN sectoral forums as arenas for maritime economic diplomacy.